ACTIVITY OF BENZOPHENONE GLUCOSIDE FROM MAHKOTA DEWA Phaleria macrocarpa (Scheff.) Boerl. FRUITS ON PROLIFERATION OF HUMAN CERVICAL-CANCER CELLS (HeLa and CasKi) AND HUMAN ESOPHAGEAL CANCER CELLS (TE-2, TE-8, and TE-14) - A. Diantini -; A. Subarnas -; T.H. Achmad -; Supriyatna -; D. Kurnia -; A. Faried -; L.S Faried -; H. Hayashi - (Direktorat Sumber Daya Akademik dan Perpustakaan, 2008)
Phaleria macrocarpa, locally named mahkota dewa, is known as a medicinal plant in Indonesia. Fruits of this plant are traditionally used in treatment of cancer diseases. Several substances were isolated from mahkota dewa fruits. A benzophenone glucoside, 4,6`-dihydroxy-4`-methoxybenzophenone-2’-O-glucoside, has been isolated from an ethyl acetate fraction of mahkota dewa fruits. The structure of this compound was determined based on the analysis of UV, IR, NMR and MS spectral data. Antiproliferative activity was measured on human cervical cancer cells (HeLa and CasKi) and human esophageal cancer cells (TE-2, TE-8, and TE-14) by MTT assay. The result of this study showed that at concentration of 500 ìg/mL, benzophenone glucoside derived from mahkota dewa didn’t reach CPI50 to all tested cells. Those CPI50 were 34 ìg/mL (HeLa), 32 ìg/mL (CasKi), 33.91 ìg/mL (TE-2), 35.43 ìg/mL (TE-8), 43.04 ìg/mL (TE-14). There were no significantly differences (á=0.5) of this activity among HeLa, CasKi, TE-2, TE-8 and TE-14 cells.Key words : Benzophenone glucoside, Phaleria macrocarpa, HeLa, CasKi, TE-2, TE-8, and TE-14 cells, MTT assay